Label-Free Imaging of Single Proteins Secreted from Living Cells via iSCAT Microscopy - Gemeinhardt, André; McDonald, Matthew P.; König, Katharina; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Journal of Visualized Experiments, 2018)
We demonstrate interferometric scattering (iSCAT) microscopy, a method capable of detecting single unlabeled proteins secreted from individual living cells in real time. In this protocol, we cover the fundamental steps to realize an iSCAT microscope and complement it with additional imaging channels to monitor the viability of a cell under study. Following this, we use the method for real-time detection of single proteins as they are secreted from a living cell which we demonstrate with an immortalized B-cell line (Laz388). Necessary steps concerning the preparation of microscope and sample as well as the analysis of the recorded data are discussed. The video protocol demonstrates that iSCAT microscopy offers a straightforward method to study secretion at the single-molecule level.
EVALuna2:35094